The some theoretical problems of definition of the structural composition of administrative procedural legal relations - Artemenko, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article are focused of the complex of structural-functional analyses of the composition of administrative procedural legal relations; as a result the author has formulated conclusions useful for the theory of administrative procedural law in general. It was analyzed the scientific approaches to the perception of the administrative procedural legal relations and formulated their definition with regard to the contemporary state of their development. The interrelations of administrative procedural legal relations with other types of legal relations are made clear.Also the theoretical separate problems of the definition internal structural of judicial relationships in administrative procedural law in particular basement elements – contact, object, subjective composition are defined. After that, the author provides specific features of administrative procedural legal relations, which, in her opinion, directly affect the range and the characteristics of their subjects. Certain administrative and procedural legal relations arise within each type of administrative process, which are clearly outlined by legal norms and provide the recommended range of their subjects, a list of procedural rights and duties of which is provided by the legislator. According to the fundamental researches of main scientists in different branches of law the contact of administrative procedural legal relationships are depicted.